PENDIDIKAN KARAKTER KEAGAMAAN-KEBANGSAAN BERBASIS KETELADANAN - Nita Agustina Nurlaila Eka Erfiana (Universitas Muhammadiyah Ponorogo, 2017)
Example Kyai Hashim Ash'ari very relevant educational materials used as the religious-national character. The example could be included as Subjects divided Islamic education and Manners Classes Five SD/MI, in accordance with the annex to the Regulation-24 the Minister of education and culture of the Republic of Indonesia Number 24, 2016, core competencies for social attitudes requires the existence of a relationship between religious character (honesty in building social interaction) and love the motherland. The regulation has limitations in providing learning materials. The only use of the regulatory acts of the Prophet as an exemplary figure for religious and nationality characters exemplify. The disadvantage is that only materials provide a character one religion with learners. The use of figures can mask the weakness of Kyai Hashim. As scholars and national hero, Kyai Hashim is a character that one religion and one country with learners in the context of Indonesia.